INFLUENCE OF INCORPORATED LABLAB PLANTED AT VARIOUS SPACINGS ON PRODUCTIVITY OF MAIZE (ZEA MAYS L.) VARIETIES IN NORTHERN GUINEA SAVANNA ZONE OF NIGERIA (FUDMA JOURNAL OF SCIENCES, 2020)
The study was conducted to evaluate the effect of incorporated lablab planted at various spacings on productivity of two maize (Zea mays L.) varieties in northern Guinea Savanna zone of Nigeria. Field experiment was carried out at the Research Farm of the Institute for Agricultural Research, Ahmadu Bello University, Zaria, Nigeria. The treatments consisted of two varieties of maize (SAMMAZ 28 and SAMMAZ 29) and six green manure lablab (Lablab purpureus) plant spacings viz. 25cm x 10cm, 25cm x 20cm, 25cm x 30cm, 50cm x 10cm, 50cm x 20cm and 50cm x 30cm. The experiment was laid out in a Randomized Complete Block Design (RCBD) in factorial arrangement and was replicated three times. SAMMAZ 29 performed significantly (P
Keywords: Incorporation, Spacing, Lablab, Maize, Variety, Productivity